A TRADITION OF INTERFAITH NYADRAN AS A MODEL OF PERSERVING SOSIAL HARMONY - Carolus Borromeus Mulyatno (P3TK, Sanata Dharma University, 2022)
This qualitative research with a phenomenological approach aims to describe nyadran as a tradition that is a means for the community to preserve a harmonious life together. Used observation and interview methods to collect data related to the nyadran ceremony. Observations were carried out to get an idea of the process of the nyadran ceremony. Next, the researcher interviewed three respondents who had experience preparing and carrying out the nyadran tradition in the Sorowajan hamlet, Banguntapan sub-district, and Bantul district. The data are analyzed using the essential elements of harmony in studying Javanese philosophy. There are three critical findings from this study. First, the Sorowajan hamlet community holds a nyadran ceremony annually involving interfaith community members. Second, the nyadran ceremony is a means to maintain and preserve the harmony of the Sorowajan community through ritual ceremonies that unite adherents of different religions. Third, the nyadran ceremony in the Sorowajan hamlet is a local tradition that has developed into a celebration of togetherness that involves people from different religious backgrounds and beliefs. Members of the community of interfaith and theology work together and are responsible for the implementation of the nyadran ceremony in a solemn and lively manner for the realization of a harmonious life together in the unity of Indonesia, which has diversity in religion, belief, ethnicity, race, culture, and local wisdom.